Contribution of flavonoids to the overall radical scavenging activity of olive (Olea europaea L.) leaf polar extracts - Goulas, Vlasios; Papoti, Vassiliki T.; Exarchou, Vassiliki; Tsimidou, María Z.; Gerothanassis, Ioannis P. (My University, 2010)
The contribution of flavonoids to the overall radical scavenging activity of olive leaf polar extracts, known to be good sources of oleuropein related compounds, was examined. Off line and on line HPLC-DPPH" assays were employed, whereas flavonoid content was estimated colorimetrically. Individual flavonoid composition was first assessed by RP-HPLC coupled with diode array and fluorescence detectors and verified by LC-MS detection system. Olive leaf was found a robust source of flavonoids regardless sampling parameters (olive cultivar, leaf age or sampling date). Total flavonoids accounted for the 13-27% of the total radical scavenging activity assessed using the on line protocol. Luteolin 7-O-glucoside was one of the dominant scavengers (8-25%). Taking into consideration frequency of appearance the contribution of luteolin (3-13%) was considered important, too. Our findings support that olive leaf, except for oleuropein and related compounds, is also a stable source of bioactive flavonoids.
Keywords: Flavonoids; Luteolin; Olive (Olea europaea L.) leaves; On line HPLC-DPPH; Radical scavenging activity